2012
DOI: 10.1021/ac202445g
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Microfluidic Devices Containing Patterned Microwell Arrays

Abstract: A rapid fabrication and prototyping technique to incorporate microwell arrays with sub-10 μm features within a single layer of microfluidic circuitry is presented. Typically, the construction of devices that incorporate very small architecture within larger components has required the assembly of multiple elements to form a working device. Rapid, facile production of a working device using only a single layer of molded polydimethylsiloxane (PDMS) and a glass support substrate is achieved with the reported fabr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…In other studies, wells at the floor of the microchannel are used to sequester and array microbeads to construct the probe library. 17,18,[22][23][24] In the well geometry, target only streams over the top part of the microbead, and at high Pe thin boundary layers cannot encircle a large portion of the microbead. As a result, diffusive transport is hindered, and one solution which is proposed is to create drains in the wells to enhance convection around the microbead.…”
Section: The Effect Of the Trap On The Mass Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies, wells at the floor of the microchannel are used to sequester and array microbeads to construct the probe library. 17,18,[22][23][24] In the well geometry, target only streams over the top part of the microbead, and at high Pe thin boundary layers cannot encircle a large portion of the microbead. As a result, diffusive transport is hindered, and one solution which is proposed is to create drains in the wells to enhance convection around the microbead.…”
Section: The Effect Of the Trap On The Mass Transfermentioning
confidence: 99%
“…Two common methods for arraying microbeads in a microfluidic cell are by using wells patterned into the bottom surface of the cell, e.g., Duffy et al 17 and Ramsey et al 18 or traps arranged as a microfluidic obstacle course, e.g., Nehorai et al 19,20 and our prior study on arraying lipobeads. 21 Well deposition has also been enhanced by using electric and magnetic fields to assist in the capture, [22][23][24] or by using holes placed in the well and connected to a drain to provide fluid suction (see McDevitt et al 25,26 and Ketterson 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…To address this need, several devices have been developed that utilized hydrodynamic flow and physical obstacles 19,20 , dielectrophoresis 21,22 , microwells 23,24 , micropatterning 25 , acoustic waves 26 and droplet encapsulation 22,2729 to precisely place individual cells in defined compartments and allow single cell measurements. Specifically, many groups have used a combination of carefully controlled flow and physically defined cell traps to offer an experimentally simple, passive and generalizable method of placing cells in defined physical locations 19,20,23 .…”
Section: Spatial Positioning Of Single Cells and Whole Organismsmentioning
confidence: 99%
“…11 Henley et al showed a microwell structure, which was fabricated by focused ion beam, and then, applied it for constructing the bead array to perform a sandwich immunoassay to analyze cytokines on the captured beads. 12 Sivagnanam et al reported in situ micropatterning of streptavidin-coated microbeads inside a microchannel using electrostatic self-assembly technique and used it for microbead based immunoassay to detect IgG antigen. 13 Burger et al presented a centrifugal microdevice for improving the microbead trap efficiency by implementing V-cup barriers in the channel.…”
Section: Introductionmentioning
confidence: 99%
“…16 Although the previous microbead array formats are adequate for sensitive biochemical analysis in a high-throughput manner without cross-contamination between beads, most of their designs were restricted to microwell structure. [8][9][10][11][12][13][14][15][16][17][18] Such a microwell structure mainly depends on the passive immobilization of the beads into each microwell, which is time-consuming, and suffers from the bead aggregate formation, leading to the non-uniform distribution of single beads in each chamber. In addition, the recovery of the immobilized beads is very difficult using the microwell array.…”
Section: Introductionmentioning
confidence: 99%